Peran Guru Kelas Madrasah Ibtidaiyah dalam Penguatan Pendidikan Karakter (Suatu Kajian Konseptual Terkait Perpres No 87 Tahun 2017) - Zuri Pamuji (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2017)
Strengthening Character Education (SCE) is a movement of education under the responsibility of educational units to strengthen the character of students through harmonization of the heart, taste, thought, and sport with the involvement and cooperation between educational unit, family, and community as part of National Movement of the Mental Revolution. The Policy on the Strengthening of Character Education Movement is set out in Presidential Decree No. 87 of 2017. This policy needs to be responded promptly systematically and comprehensively by every stakeholders in the educational institution, including the school. One among the stakeholders who have an important role in the strengthening of Charater education is the classroom teacher in Madrasah Ibtidaiyah. As for alternative the role of classroom teachers in the movement can be done by fostering psychological atmosphere in the classroom and school, integrate character in curricular activities, and integrate character in the co-curiruler activities.